Coexpression of VHb and MceG genes in Mycobacterium sp. Strain LZ2 enhances androstenone production via immobilized repeated batch fermentation. (December 2021) - Zhang, Yang; Zhou, Xiuling; Yao, Yingying; Xu, Qianqian; Shi, Haiying; Wang, Kuiming; Feng, Wei; Shen, Yanbing
Highlights: Coexpression of vgb and mceG enhances the growth and productivity of Mycobacterium . Coexpression reduces intracellular ROS levels and increases cell viability. Bagasse is an excellent immobilization carrier for recombinant bacteria. Immobilized culture increases the substrate tolerance of recombinant bacteria. Production increased by 1.82 times using immobilized repeated batch fermentation. Abstract: Androstenone production is limited by low-efficiency substrate transport and dissolved oxygen levels during fermentation. In this study, the coexpression of the optimized Vitreoscilla hemoglobin (VHb) and sterol transporter ATPase (MceG) genes in Mycobacterium sp. LZ2 (Msp) was investigated to alleviate dissolved oxygen and mass transfer limitations. Results revealed that Msp- vgb / mceG effectively improved the growth, production, and adaptation to dissolved oxygen compared with those of Msp. The increased catalase activity and reduced intracellular ROS levels enhanced cell viability and promoted transcription of genes critical for phytosterol metabolism. Bagasse as an immobilization carrier increased the productivity of Msp- vgb / mceG by 56%. Immobilized repeat batch fermentation reduced the biotransformation period from 60 days to 37 days and improved the productivity from 0.039 g/L/h to 0.069 g/L/h. To the best of our knowledge, this work is the first study on the immobilization of recombinant mycobacteria on bagasse for androstenone production.